Laser transmission welding method for in-situ strengthening of welds

By using low-cost semiconductor lasers and simply prepared metal ion coatings for transparent plastic welding, the problems of thermal damage and environmental pollution in existing technologies are solved, and high-performance transparent plastic welding is achieved.

CN120396366BActive Publication Date: 2025-09-12SUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510884752.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-09-12
Estimated Expiration
2045-06-30

AI Technical Summary

Technical Problem

Existing transparent plastic welding technology has problems such as long-wavelength laser thermal damage, high cost of ultrafast laser equipment, complex preparation of visible light-near-infrared short-wavelength laser coating, environmental pollution and decreased mechanical properties of the joint.

Method used

Transparent plastic welding is performed using low-cost semiconductor lasers and simply prepared metal ion coatings. The ion coating is used to in-situ form nanomaterials during the welding process to enhance the mechanical properties of the joint.

Benefits of technology

It realizes low-cost and environmentally friendly transparent plastic welding, reduces assembly positioning requirements, improves the strength and quality of welds, and avoids environmental pollution and thermal damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120396366B_ABST
    Figure CN120396366B_ABST
Patent Text Reader

Abstract

The present invention relates to a laser transmission welding method for in-situ strengthening of welds, and belongs to the field of laser welding technology. The laser transmission welding method of the present invention comprises the following steps: washing a first transparent substrate to be welded and a second transparent substrate to be welded with deionized water and anhydrous ethanol respectively, and then drying; mixing a metal salt and a reducing ligand in a solvent to obtain a metal ion solution; coating the obtained metal ion solution on the first transparent substrate to be welded, heating and drying to obtain a transparent substrate containing an ion coating; subjecting the obtained transparent substrate containing an ion coating to laser scanning pretreatment; laminating the obtained transparent substrate to the second transparent substrate to be welded, with the laminating surface being the side containing the copper ion coating; adjusting the laser, and performing laser welding using the same laser route. By utilizing nanomaterials formed in situ by the chemical reaction of the ion coating to enhance the mechanical properties of the joint, a high-performance joint can be obtained while solving existing problems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser welding, and in particular relates to a laser transmission welding method for in-situ strengthening of welds. Background Art

[0002] Transparent plastics have the characteristics of being light and portable, highly chemically stable, and having excellent optical properties. They are widely used in aerospace, medical, communications, electronics and other fields. In the processing of plastic products, due to the limitations of factors such as the injection molding process, many complex components cannot be injection molded in one go, and often require multiple parts to be bonded together. There are many traditional ways of connecting plastics, such as friction welding, which uses friction to generate heat to melt the plastic contact surfaces, and then applies pressure to connect them together; hot melt welding, which uses a heating tool to heat the plastic to a molten state, and then applies pressure to connect them. However, the above methods usually rely on specific molds and are difficult to meet the needs of customizable flexible manufacturing. In contrast, laser transmission welding technology is a contactless welding technology with the advantages of fast welding speed, small heat action area, and high precision. It has broad application prospects in the field of plastic processing.

[0003] Because transparent plastics typically absorb mid-infrared light strongly, long-wavelength lasers (such as 10.6 μm CO2 lasers) can be used for direct welding. However, the high thermal stress of these lasers can easily cause thermal damage to the plastic. Ultrafast lasers are another viable approach for welding transparent plastics. Their principle, based on two-photon absorption, enables electrons to transition from the ground state to a higher excited state, achieving material welding. While they offer advantages such as low thermal stress and high precision, their application is limited by the high cost of the equipment. Furthermore, these methods require precise focusing of the laser on the interface of the plastics being welded, placing extremely high demands on processing, assembly, and positioning.

[0004] Visible-near-infrared short-wavelength lasers have attracted widespread attention in recent years due to their low cost and minimal welding positioning requirements (the base material itself does not absorb light). Because transparent materials have low absorption rates for visible and near-infrared light, welding transparent plastics using these wavelengths typically requires the addition of an additional coating as a light absorber at the interface. Current coating preparation processes are technically demanding, requiring complex reaction conditions such as separation, purification, cleaning, and drying (as exemplified by the core-shell microspheres disclosed in patent CN101903182 B). Furthermore, some coatings contain hazardous substances (such as carbon black in the light absorber disclosed in patent CN105968566 B), making it difficult to avoid health and environmental risks during processing and making them unsuitable for applications requiring high cleanliness. Furthermore, most current coatings offer limited functionality, lacking any strength in the resulting weld and even introducing impurities that degrade joint performance.

[0005] In summary, the existing technologies have the following disadvantages: long-wavelength laser transmission welding can easily cause thermal damage to the material, and ultrafast laser equipment is expensive; visible light-near-infrared short-wavelength lasers are low-cost and widely applicable, but the preparation process of the coatings currently used is complex, easy to pollute the environment, and will lead to a decrease in the mechanical properties of the joint. Summary of the Invention

[0006] To address these technical issues, the present invention provides a laser transmission welding method for in-situ weld strengthening. This method utilizes a low-cost semiconductor laser and introduces a simple, low-cost, and environmentally friendly metal ion coating for transparent plastic welding. Furthermore, nanomaterials formed in situ by chemical reactions in the ion coating enhance the mechanical properties of the joint, achieving a high-performance joint while addressing existing challenges.

[0007] The present invention is achieved through the following technical solutions:

[0008] The object of the present invention is to provide a laser transmission welding method for in-situ strengthening of welds, comprising the following steps:

[0009] S1, washing the first transparent substrate to be welded and the second transparent substrate to be welded with deionized water and anhydrous ethanol respectively, and then drying;

[0010] S2, mixing the metal salt and the reducing ligand in a solvent to obtain a metal ion solution;

[0011] S3, coating the metal ion solution obtained in step S2 on the first transparent substrate to be welded obtained in step S1, and heating and drying the substrate to obtain a transparent substrate containing an ion coating;

[0012] S4, performing laser scanning pretreatment on the transparent substrate containing the ion coating obtained in step S3;

[0013] S5, laminating the transparent substrate obtained in step S4 to the second transparent substrate to be welded, with the laminating surface being the side containing the ion coating;

[0014] S6. Adjust the laser and perform laser welding using the same laser route as step S4.

[0015] Furthermore, in step S1, the first transparent substrate to be welded and the second transparent substrate to be welded are respectively selected from one or more of polyimide, polyethylene terephthalate and polycarbonate.

[0016] Furthermore, in step S2, the metal salt is a soluble metal salt; the soluble metal salt is selected from one or more of aluminum salts, copper salts and silver salts.

[0017] The aluminum salt is selected from one or more of aluminum nitrate, aluminum chloride and aluminum sulfate; the copper salt is selected from one or more of copper nitrate, copper sulfate and copper chloride; and the silver salt is selected from one or more of silver nitrate, silver perchlorate and silver sulfate.

[0018] Furthermore, in step S2, the reducing ligand is selected from one or more of ethylene glycol, polyethylene glycol and polyvinyl pyrrolidone.

[0019] And / or, the solvent is selected from deionized water.

[0020] Furthermore, in step S2, the volume ratio of the metal salt to the reducing ligand is 1:1-2:1. The concentration of the metal salt is 5 mol / L, and the concentration of the reducing ligand is 0.3 g / mL.

[0021] Furthermore, in step S3, the coating amount is greater than or equal to 50 μL / cm 2 .

[0022] Furthermore, in step S3, the heating condition is: heating at 70°C-80°C for 5 min-10 min.

[0023] Furthermore, in step S4, the power of the laser scanning is 0.2 W-0.4 W;

[0024] And / or, the spot diameter of the laser is 20 μm-50 μm;

[0025] And / or, the wavelength of the laser is 400 nm-1100 nm;

[0026] And / or, the laser scanning path is an orthogonal serpentine trajectory, and the gap of the scanning path is 0.02 mm-0.1 mm.

[0027] Furthermore, in step S6, the laser power is 2.5 W-3 W;

[0028] Furthermore, in step S6, the spot diameter of the laser is 100 μm-200 μm;

[0029] And / or, the wavelength of the laser is 400 nm-1100 nm.

[0030] And / or, the laser welding path is an orthogonal serpentine trajectory, and the gap of the scanning path is 0.02 mm-0.1 mm.

[0031] The above technical solution of the present invention has the following advantages over the prior art:

[0032] (1) The present invention provides a laser transmission welding method for in-situ weld strengthening. The metal ion solution used in the present invention is low-cost and simple to prepare. During the welding process, no harmful substances such as organic waste gas and smoke are generated, and the pollution to the environment is relatively small. At the same time, the coating formed can significantly improve the local short-wavelength laser absorption rate, avoid the use of expensive ultrafast laser equipment, and effectively reduce the assembly and positioning requirements of the welding process.

[0033] (2) The ion coating used in the present invention can effectively avoid the impurities introduced by the volatilization of existing light absorbers, helping to reduce defects in the weld, such as pores and slag inclusions. At the same time, the metal ions will form metal nanoparticles in situ during the welding process, forming a pinning effect in the weld to enhance the joint strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0035] Figure 1 This is the surface morphology of the area to be welded obtained after laser pretreatment in Example 1 of the present invention;

[0036] Figure 2 This is the macroscopic morphology of the welding sample in Example 1 of the present invention;

[0037] Figure 3 is the cross-sectional morphology of the welding sample under the preferred parameter conditions in Example 2 of the present invention;

[0038] Figure 4 This is the macroscopic morphology of the welding sample under excessive laser input in Comparative Example 2 of the present invention;

[0039] Figure 5 is the shear strength of the joint under different laser energy inputs in the test example of the present invention;

[0040] Figure 6 This is the cross-sectional morphology of the sample directly welded without pretreatment in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0041] The present invention will be further described below with reference to the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. However, the embodiments are not intended to limit the present invention.

[0042] The invention discloses an ionic coating prepared by mixing metal salt, reducing agent and solvent in a certain proportion, which absorbs laser energy and forms a nano-reinforced phase in situ in the weld; and also discloses a laser transmission welding method thereof.

[0043] (1) Cutting the transparent plastic to be welded into the required size and cleaning the surface to obtain a first transparent substrate to be welded and a second transparent substrate to be welded;

[0044] (2) Mixing metal salt, reducing agent, and solvent in a certain proportion to obtain a metal ion solution;

[0045] (3) applying the metal ion solution to the first transparent substrate to be welded and drying it to obtain an ionic coating;

[0046] (4) Use focused laser to pre-treat it to remove excess ligands to avoid introducing defects such as holes during subsequent welding. This process also produces the conversion of some metal ions into nanoparticles;

[0047] (5) Overlap the second transparent substrate to be welded with the plastic after the above treatment, pre-tighten it by a clamp to make it fit tightly, and perform laser scanning again to complete the welding.

[0048] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are all commercially available unless otherwise specified.

[0049] Example 1:

[0050] This embodiment provides a method for laser welding transparent materials using an ionic coating, comprising the following steps:

[0051] (1) Cut the transparent polyimide into 1 cm × 4 cm pieces and wash them with deionized water and anhydrous ethanol before use;

[0052] (2) Mix 6 mol / L aluminum nitrate solution and 0.3 g / mL polyethylene glycol solution in a 1:1 volume ratio;

[0053] (3) 50 μL of the mixed solution was drop-coated on the area to be welded (1 cm × 1 cm) on the polyimide surface and heated at 80 °C for 10 min to obtain an ionic coating.

[0054] (4) A 450 nm laser was used for pretreatment, with a power of 0.3 W and a spot diameter of 50 μm. The area to be welded was scanned in a serpentine trajectory with a scanning interval of 30 μm.

[0055] (5) Place a second transparent plastic sheet of the same size on top of the first sheet, with an overlapping area of ​​1 cm × 1 cm, ensuring a tight fit between the two.

[0056] (6) A 450 nm laser was used with a power of 3 W and a spot diameter of 100 μm. The area to be welded was scanned in a serpentine trajectory with a scanning interval of 30 μm to complete the welding.

[0057] Figure 1 This is the surface morphology of the welded area after laser pretreatment in this embodiment. It can be observed that a large number of in-situ synthesized nanoparticles exist, which is beneficial to improving the mechanical properties of the final joint. Figure 2 This is the macroscopic morphology of the welding sample obtained in this embodiment, from which it can be seen that the surface is smooth, indicating that the joint is well formed.

[0058] Example 2:

[0059] This embodiment provides a method for laser welding transparent materials using an ionic coating, comprising the following steps:

[0060] (1) Cut the transparent polyimide into 1 cm × 4 cm pieces and wash them with deionized water and anhydrous ethanol before use;

[0061] (2) Mix 6 mol / L copper nitrate solution and 0.3 g / mL polyethylene glycol solution in a 1:1 volume ratio;

[0062] (3) 50 μL of the mixed solution was drop-coated on the area to be welded (1 cm × 1 cm) on the polyimide surface and heated at 80 °C for 10 min to obtain an ionic coating.

[0063] (4) An 808 nm laser was used for pretreatment, with a power of 0.3 W and a spot diameter of 30 μm. The area to be welded was scanned in a serpentine trajectory with a scanning interval of 30 μm.

[0064] (5) Place a second transparent plastic sheet of the same size on top of the first sheet, with an overlapping area of ​​1 cm × 1 cm, ensuring a tight fit between the two.

[0065] (6) An 808 nm laser was used with a power of 3 W and a spot diameter of 100 μm. The welding area was scanned in a serpentine trajectory with a scanning interval of 30 μm to complete the welding.

[0066] Figure 3 The cross-sectional micromorphology of the welded joint obtained in this embodiment shows that the upper and lower parent materials are connected by a clear fusion line, and no defects such as pores and ablation are observed, indicating that the welded joint obtained by this technical solution is of high quality.

[0067] Example 3:

[0068] This embodiment provides a method for laser welding of transparent materials using an ionic coating, which is similar to Example 2, except that in step (6), the laser power is 2.5 W, and the other operations remain the same.

[0069] Comparative Example 1:

[0070] This comparative example provides a method for laser welding transparent materials using an ionic coating. The method is similar to Example 2, except that the laser welding power in step (6) is changed to 1.5 W, while the other operations remain the same. The results show that when the laser welding power is 1.5 W, no effective weld can be formed, indicating that sufficient laser energy input is required.

[0071] Comparative Example 2:

[0072] This comparative example provides a method for laser welding transparent materials using ionic coatings. The method is similar to Example 2, except that the laser welding power in step (6) is changed to 5 W, and the other operations remain the same. The results are as follows: When the laser welding power is 5 W, the surface morphology of the obtained sample is as follows: Figure 4 As shown, it can be seen that the surface is rough, indicating that excessive energy input causes thermal damage to the plastic substrate.

[0073] Comparative Example 3:

[0074] This comparative example provides a method for laser welding of transparent materials using an ionic coating, which is similar to Example 2, except that the laser welding power in step (6) is changed to 2 W, and the other operations remain the same.

[0075] Comparative Example 4:

[0076] This comparative example provides a method for laser welding transparent materials using an ionic coating, which is similar to Example 2, except that the laser welding power in step (6) is changed to 3.5 W, and the other operations remain the same.

[0077] Comparative Example 5:

[0078] This comparative example provides a method for laser welding of transparent materials using an ionic coating, which is similar to Example 2, except that the laser welding power in step (6) is changed to 4 W, and the other operations remain the same.

[0079] Test example:

[0080] For Example 2, Example 3 and Comparative Examples 3-5, the mechanical properties of the joints obtained with a laser power of 2-4 W were tested using a universal tensile testing machine. Figure 5 As shown in the figure, the shear strength of the joint is as high as 120 MPa at a laser power of 2.5-3 W, and the joint finally breaks at the position of the parent material, indicating its excellent mechanical properties.

[0081] Comparative Example 6:

[0082] This comparative example provides a method for laser welding of transparent materials, which is similar to Example 2, except that the laser scanning pretreatment step (4) is omitted and laser welding is performed directly. The cross-sectional morphology of the obtained joint is as follows: Figure 6 As shown, it can be seen that there are a lot of pores in the weld, which is caused by the ineffective discharge of the reducing agent in the ion coating during the direct welding process, indicating that the laser scanning pretreatment step is necessary.

[0083] Comparative Example 7:

[0084] This comparative example provides a method for laser welding transparent materials using an ionic coating. The method is similar to Example 2, except that the amount of the mixed solution applied in step (3) is reduced to 5 μL, and the strength of the resulting joint is tested using the method described in the test example. The results show that although the ionic coating can also act as a light absorber to complete the welding after a large amount of addition, the joint strength is only 50 MPa, which proves that the reinforcing effect introduced by the coating on the weld is significant.

[0085] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will appreciate that other variations or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A laser transmission welding method for in-situ strengthening of welds, characterized in that: The following steps are involved: S1, washing the first transparent substrate to be welded and the second transparent substrate to be welded with deionized water and anhydrous ethanol respectively, and then drying; S2, mixing the metal salt and the reducing ligand in a solvent to obtain a metal ion solution; S3, coating the metal ion solution obtained in step S2 on the first transparent substrate to be welded obtained in step S1, and heating and drying the substrate to obtain a transparent substrate containing an ion coating; S4, performing laser scanning pretreatment on the transparent substrate containing the ion coating obtained in step S3; S5, laminating the transparent substrate obtained in step S4 to the second transparent substrate to be welded, with the laminating surface being the side containing the ion coating; S6, adjusting the laser and performing laser welding using the same laser route as step S4; In step S6, the laser power is 2.5 W-3 W; In step S2, the volume ratio of the metal salt to the reducing ligand is 1:1-2:1; In step S3, the coating amount is greater than or equal to 50 μL / cm 2 ; In step S4, the power of the laser scanning is 0.2 W-0.4 W.

2. The laser transmission welding method according to claim 1, characterized in that: In step S1, the first transparent substrate to be welded and the second transparent substrate to be welded are respectively selected from one or more of polyimide, polyethylene terephthalate and polycarbonate.

3. The laser transmission welding method according to claim 1, characterized in that: In step S2, the metal salt is a soluble metal salt; the soluble metal salt is selected from one or more of aluminum salts, copper salts and silver salts.

4. The laser transmission welding method according to claim 1, characterized in that: In step S2, the reducing ligand is selected from one or more of ethylene glycol, polyethylene glycol and polyvinyl pyrrolidone; And / or, the solvent is selected from deionized water.

5. The laser transmission welding method according to claim 1, characterized in that: In step S3, the heating condition is: heating at 70° C.-80° C. for 5 min-10 min.

6. The laser transmission welding method according to claim 1, characterized in that: In step S4, the spot diameter of the laser is 20 μm-50 μm; And / or, the wavelength of the laser is 400 nm-1100 nm; And / or, the laser scanning path is an orthogonal serpentine trajectory, and the gap of the scanning path is 0.02 mm-0.1 mm.

7. The laser transmission welding method according to claim 1, characterized in that: In step S6, the spot diameter of the laser is 100 μm-200 μm; And / or, the wavelength of the laser is 400 nm-1100 nm; And / or, the laser welding path is an orthogonal serpentine trajectory, and the gap of the scanning path is 0.02 mm-0.1 mm.

Citation Information

Patent Citations

  • Microsphere comprising a polymer core, a shell and an absorber, use and preparation method thereof

    CN101903182B

  • Preparation method of absorbent for laser transmission welding of transparent plastics

    CN105968566B

  • Method for enhancing laser transmission welding strength of thermoplastic plastic

    CN120080553A